"Learning from craft taxonomies: development and a Yoruba textile tradition. " (1995)
The value of eliciting .taxonomies to reveal the local knowledge of local communities about their natural and cultural world has been appreciated by anthropologists and developers for several decades. Craft taxonomies receive little attention, despite the role they play in structuring the indigenous knowledge which underlies handicraft industries in the informal sector of developing economies. The resilience of Yoruba indigenous hand-woven cloth industries has been proven again and again, as forces of change have tested the readiness of weavers to adapt to shifts in taste, competition from outside markets, "changing technologies, and the lure of modern-sector occupations. Although the textile taxonomy presented in this article is preliminary and still in progress, it is an example of indigenous knowledge in action, where choices are constantly being made on the basis of contemporary tastes and markets.